Produkcja wyrobów tytoniowych - Kapusta, Franciszek (Production of Tobacco Products, 2007)
The habit of chewing or smoking tobacco has long history. It came to Europe in the 16th century after the discovery of America. The spreading use of tobacco caused many counter-actions. Prolonged smoking of tobacco causes nicotine addiction. In the 17th century tobacco came to Poland and in the 18th century first plantations and production plants were created. In 1786 monopoly of production and sales was imposed and renewed in 1922. Production of tobacco in Poland has been changing. The largest area and crops were in 1980. Later, due to various reasons, the production decreased. Similar tendency, but not so strong as in Poland, is present in the world. According to demand, the production of tobacco as well as its structure are changing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Technologia (12); 2007; nr 1172, s. 20-27